2008
DOI: 10.1590/s1135-57272008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Atlas interactivo de mortalidad en Andalucía (AIMA)

Abstract: Until now, mortality atlases have been static. Most of them describe the geographical distribution of mortality using count data aggregated over time and standardized mortality rates. However, this methodology has several limitations. Count data aggregated over time produce a bias in the estimation of death rates. Moreover, this practice difficult the study of temporal changes in geographical distribution of mortality. On the other hand, using standardized mortality hamper to check differences in mortality amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Our conclusion critically questions previous ecological/spatial studies of small-area variation published hitherto in Spain (Benach et al, 2003;Benach et al, 2004;Borrell et al, 2010;Collaboration, 2010;Ocana-Riola & Mayoral-Cortes, 2010;Ocana-Riola et al, 2008a). These ecological/spatial studies of small-area variation are only justified if we implicitly assume that the geographical variation between municipalities and between census tracts represents an important factor for understanding individual inequalities in mortality risk.…”
Section: General Contextual Effects: On Geographical Variationmentioning
confidence: 52%
See 1 more Smart Citation
“…Our conclusion critically questions previous ecological/spatial studies of small-area variation published hitherto in Spain (Benach et al, 2003;Benach et al, 2004;Borrell et al, 2010;Collaboration, 2010;Ocana-Riola & Mayoral-Cortes, 2010;Ocana-Riola et al, 2008a). These ecological/spatial studies of small-area variation are only justified if we implicitly assume that the geographical variation between municipalities and between census tracts represents an important factor for understanding individual inequalities in mortality risk.…”
Section: General Contextual Effects: On Geographical Variationmentioning
confidence: 52%
“…However, many multilevel analyses performed so far have been mainly focused on the study of associations between contextual variables and individual health, considering the analysis of variance as secondary information (Blakely & Woodward, 2000;Diez Roux, 2008). In contrast, others scholars have explicitly concluded that the analysis of variance provides indispensable information for understanding place effects on health (Boyle MH & Willms JD, 1999;Clarke P & Wheaton B, 2007;Duncan et al, 1993;Merlo, 2003;Merlo et al, 2004;Merlo et al, 2009;Riva et al, 2007) Moreover, all around the world, a persistent amount of observational information on place effects is still being obtained from ecological/spatial studies of "small-area variations" , frequently in the form of coloured atlases and disease maps (Benach et al, 2003;Benach et al, 2004;Borrell et al, 2010;Collaboration, 2010;MacNab & Dean, 2002;Middleton et al, 2008;Ocana-Riola & Mayoral-Cortes, 2010;Ocana-Riola et al, 2008a;Pickle et al, 1999;Shaw, 2008;Turrell & Mengersen, 2000). From an empirical perspective, the advantages of multilevel versus ecological regression analyses were clearly identified by the seminal work performed by Aitkins and Longford (Aitkin M & Longford N, 1986) as well as by Jones,4 Duncan, Moon, Subramanian and colleagues (Bullen et al, 1996;Duncan et al, 1993Duncan et al, , 1995Duncan et al, , 1996Duncan et al, , 1998Duncan et al, , 1999Jones et al, 1991;Subramanian et al, 2009;Twigg et al, 2000).…”
mentioning
confidence: 99%
“…Dynamic mortality maps are able to provide up-to-date understanding of the geographical variation and evolution over time of mortality from breast cancer and other causes of death, substantially improving on the information provided by conventional static atlases [32]. However, a systematic validation of the information sources, a careful statistical analysis and a thorough interpretation of mortality maps are all still needed in epidemiological research.…”
Section: Discussionmentioning
confidence: 99%
“…The reader interested in the published studies on other causes of death in Andalusia, or methodological aspects related to disease mapping, can obtain additional information from the references at the end of this paper [9,23,30,31,32], as well as at the DEMAP web site [33]. The conclusions of these studies have been cited, in part, during the discussion of this paper and together can help to understand the evolution of mortality in Andalusia over both space and time.…”
Section: Discussionmentioning
confidence: 99%
“…El Atlas Interactivo de Mortalidad en Andalucía se implementó en esta regió n con fines de vigilancia epidemioló gica 14 . Los aná lisis de los datos actualizados anualmente del Atlas Interactivo de Mortalidad en Andalucía aportan una perspectiva respecto a la distribució n geográ fica de la mortalidad por cardiopatía isqué mica a lo largo del tiempo en el sur de Españ a. Estudios recientes basados en esos datos indican que, actualmente, en má s del 95% de los municipios andaluces las tasas de mortalidad de varones y mujeres de los grupos de menos de 65 añ os de edad son similares o significativamente inferiores a las correspondientes tasas españ olas.…”
Section: Introducció Nunclassified